SPATIAL VARIABILITY OF ORGANIC CARBON STOCKS IN SEAGRASS ECOSYSTEMS: THE ROLE OF BIOMASS AND SEDIMENTS IN BANYAK ISLANDS, ACEH SINGKIL - Lisdayanti, Eka; Najmi, Nurul; Akmal, Abdiel Khaleil; Nasution, Anisah; Nasution, Muhammad Arif (LPPM Universitas Jambi, 2026)
Seagrass ecosystems are major blue carbon reservoirs that play an important role in climate change mitigation, yet their capacity is increasingly threatened by anthropogenic pressures in tropical coastal areas such as Banyak Islands, Aceh Singkil. This study aimed to analyse organic carbon (Corg) content and estimate the carbon storage potential of seagrass ecosystems in this region. Field data were collected using line transect and quadrat methods in intertidal and subtidal zones to assess seagrass cover and species composition, while organic carbon in biomass and sediments was analysed using the Loss on Ignition (LOI) method. The results showed significant spatial variation in carbon storage. The highest biomass carbon was recorded at Rago-rago Island, dominated by Thalassia hemprichii (20.26% cover), whereas the highest sediment organic carbon was found at Balai Island, dominated by Cymodocea rotundata (1.37% cover). Sediments were identified as the primary carbon reservoir (4.15 Mg Corg ha⁻¹), while biomass contributed a smaller proportion (0.71 Mg Corg ha⁻¹). These differences are influenced by species morphology, sediment characteristics, and hydrodynamic conditions. This study highlights the dominant role of sediments in seagrass carbon storage and the importance of ecosystem structure in regulating carbon sequestration. The findings provide quantitative evidence to support blue carbon–based conservation strategies and ecosystem-based coastal management for climate change mitigation in western Indonesia.